Narratives as Sources of Stability and Change in Organizations: Approaches and Directions for Future Research. Issue 1 (1st January 2016) - Vaara, Eero; Sonenshein, Scott; Boje, David
Abstract: Although narrative analysis has made significant advances in organization and management studies, scholars have not yet unleashed its full potential. This review provides an understanding of key issues in organizational narrative analysis with a focus on the role of narratives in organizational stability and change. We start by elaborating on the characteristics of organizational narratives to provide a conceptual framework for organizational narrative analysis. We elaborate on three key approaches to narrative analysis on stability and change: realist, interpretative, and poststructuralist. We then review several topic areas where narrative analysis has so far offered the most promise: organizational change, identity, strategy, entrepreneurship, and personal change. Finally, we identify important issues that warrant attention in future research, both theoretically and methodologically.